2021
DOI: 10.1186/s12981-021-00398-0
|View full text |Cite
|
Sign up to set email alerts
|

HIV Care Coordination promotes care re-engagement and viral suppression among people who have been out of HIV medical care: an observational effectiveness study using a surveillance-based contemporaneous comparison group

Abstract: Background Medical care re-engagement is critical to suppressing viral load and preventing HIV transmission, morbidity and mortality, yet few rigorous intervention studies address this outcome. We assessed the effectiveness of a Ryan White Part A-funded HIV Care Coordination Program relative to ‘usual care,’ for short-term care re-engagement and viral suppression among people without recent HIV medical care. Methods The Care Coordination Program wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Although there is some observational evidence that improved care coordination and patient navigation can have a positive impact on HIV care engagement and viral suppression [12] and also evidence for case management reducing sexual risk behaviors and syphilis among MSM with HIV [13], there is a paucity of evidence for enhanced case management having a direct effect on HIV viral suppression in rigorous controlled trials. One study showed that patient navigation, with or without financial incentives, did not have a beneficial effect on HIV viral suppression among hospitalized patients with HIV and substance use [14], with the literature suggesting that multiple factors are associated with lower odds of sustained HIV viral suppression, including demographic factors, drug and alcohol use, mental health symptoms, homelessness, transportation to appointment needs, as well as provider characteristics [15].…”
Section: Introductionmentioning
confidence: 99%
“…Although there is some observational evidence that improved care coordination and patient navigation can have a positive impact on HIV care engagement and viral suppression [12] and also evidence for case management reducing sexual risk behaviors and syphilis among MSM with HIV [13], there is a paucity of evidence for enhanced case management having a direct effect on HIV viral suppression in rigorous controlled trials. One study showed that patient navigation, with or without financial incentives, did not have a beneficial effect on HIV viral suppression among hospitalized patients with HIV and substance use [14], with the literature suggesting that multiple factors are associated with lower odds of sustained HIV viral suppression, including demographic factors, drug and alcohol use, mental health symptoms, homelessness, transportation to appointment needs, as well as provider characteristics [15].…”
Section: Introductionmentioning
confidence: 99%
“…43 The investigators suggest their null results may be tied to unrecognized commonalities between the adapted intervention and "usual care" in Baltimore. 43 It is not clear whether our trial's findings reflect a null difference in effectiveness between the revised and original CCP (which has already shown superiority to usual care 20,21,44 ) or reflect incomplete implementation of revised-CCP components during the trial. Analyses to date have not detected significant implementation variability in relation to the outcome, but our implementation measure may be insufficiently sensitive to such variability.…”
Section: Contextualization Of Null Findingsmentioning
confidence: 89%